2003
DOI: 10.1097/00126334-200304150-00011
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary HIV Testing Among Inmates: Sociodemographic, Behavioral Risk, and Attitudinal Correlates

Abstract: We sought to determine the prevalence and correlates of self-reported HIV testing among inmates in correctional centers in Ontario, Canada. A cross-sectional survey was conducted with a stratified random sample of 597 male and female adult inmates. The participation rate was 89%. Descriptive statistics and multiple logistic regression were used to analyze HIV testing. Fifty-eight percent had ever been tested, and 21% had voluntarily tested while incarcerated in the past year. Having ever been tested was more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 19 publications
3
31
2
Order By: Relevance
“…This finding is consistent with earlier findings by Burchell et al (2003) that suggest previous sexual contact or sharing needles with a known HIV positive person prior to incarceration increase the likelihood of VCT utilisation. This finding may be due to inmate's knowledge of HIV risk factors and awareness of their own risk while in the community.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with earlier findings by Burchell et al (2003) that suggest previous sexual contact or sharing needles with a known HIV positive person prior to incarceration increase the likelihood of VCT utilisation. This finding may be due to inmate's knowledge of HIV risk factors and awareness of their own risk while in the community.…”
Section: Discussionsupporting
confidence: 92%
“…This is an indication for inmates to be encouraged to undergo VCT as they have access to health care and this will assist in reducing the prevalence of HIV/AIDS in prisons as those who test negative for HIV will be given health education on issues of healthy sex practices so that they maintain their negative HIV status, and those who test positive for HIV have access to other related services like antiretroviral therapy, sexually transmitted infections (STIs) clinics and TB prevention programmes in time. A review of the literature demonstrates the reasons prisoners opt to undergo or not undergo VCT include being injecting drug users, fear of HIV infection while in prison through blood contact such as during fights, recent risky sexual behaviours or previous contact with an HI-positive person, previous HIV-positive test, low-risk lifestyle, negative HIV test 2 -12 months previously, no prior HIV test mentioned, concern over confidentiality of results, dislike of venipuncture, and release within six month (Behrendt et al, 1994;Burchell et al, 2003). Haggerty and Nesselroth (2000) also report that 'Stigmatization, the potential threat of violence, poor HIV education, and lack of confidentiality may cause many prisoners to avoid voluntary testing even when they know that they are at risk of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Female gender, younger age, and race have been positively associated with HIV testing (Bond, Lauby, & Batson, 2005;Burchell et al, 2003;Wang, Li, Stanton, & McGuire, 2010). Greater knowledge regarding HIV and a history of injection drug use were further predictors (Burchell et al;Gage & Ali, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Female gender, younger age, race, and being single are positively associated with HIV testing behavior (Bond et al 2005;Burchell et al 2003;Shuter et al 1997). Greater AIDS knowledge and higher education (Gage and Ali 2005;Stein and Nyamathi 2000), a history of an STD and injection drug use (Burchell et al 2003;Goodman and Berecochea 1994;Shuter et al 1997;Stolte et al 2003) were found to be significant predictors of having taken an HIV test. Higher perceived risk for HIV was found to be consistently associated with increased likelihood of having been tested for HIV (Downing et al 2001;Maman et al 2001;Stein and Nyamathi 2000).…”
Section: Introductionmentioning
confidence: 99%